The Effect of Accountability, Transparency, and Community Participation on Village Fund Management - Agusman Agusman; Risa Wahyuni; Taslinawati Taslinawati (Institut Agama Islam Sumatera Barat, 2023)
This study aims to: analyze the effect of accountability on the management of village funds in North Cubadak Air village, analyze the effect of transparency on the management of village funds in North Cubadak Air village and analyze community participation on the accountability of village fund management in North Cubadak Air village. This research is descriptive quantitative research. The population in this study were all village government officials and community representatives in North Cubadak Air Village, the sample taken for this study was 91 people. The sample was determined by purposive sampling technique method. Data was collected using a questionnaire and analyzed with SPSS version 26.0. The results showed that accountability has a significant effect on the management of village funds. Transparency has a significant effect on the management of village funds. Community participation has a significant effect on the management of village funds. The conclusion of this study is that accountability, transparency, community participation affect the management of village funds.